Velocity autocorrelation functions and diffusion сoefﬁcient of dusty component in complex plasmas - Dzhumagulova, K.N.; Masheeva, R.U. (Recent Contributions to Physics, 2012)
In this article the velocity autocorrelation functions of dusty particles were calculated by the Langevin dynamics. It was indicated that their oscillations decay more rapidly with increase in the friction parameters. The dependencies of the dusty particles diffusion coefﬁcient on the friction coefﬁcient at the different values of various parameters were obtained by the Green-Kubo relation and mean square displacements. The validity of the Einstein formula at small values of coupling parameter was shown.